Cortisol Response in Healthy and Diseased Dogs after Stimulation with a Depot Formulation of Synthetic ACTH. (27th October 2015) - Sieber‐Ruckstuhl, N.S.; Burkhardt, W.A.; Hofer‐Inteeworn, N.; Riond, B.; Rast, I.T.; Hofmann‐Lehmann, R.; Reusch, C.E.; Boretti, F.S.
Abstract : Background: The ACTH stimulation test is used to evaluate the adrenocortical reserve. Recently, the availability of the synthetic ACTH formulation was limited, causing major problems in clinical practice. Objectives: The objective of this study was to evaluate poststimulation peak cortisol concentrations and the duration of the stimulatory effect of a depot ACTH preparation in dogs. Animals: Twenty‐two healthy dogs, 10 dogs with suspected hypoadrenocorticism (HA) and 15 dogs with suspected hyperadrenocorticism (HC). Methods: Prospective study. An ACTH stimulation test using a synthetic depot tetracosactide, administered intramuscularly (5 μg/kg or at least 0.1 mL) was performed. Blood samples for determination of cortisol were taken immediately before and 1, 2, 3, 4, 6, and 24 hours after stimulation. Results: Peak cortisol concentrations were reached after 2–4 hours in all dogs. Cortisol concentrations 1 hour after stimulation were >9 μg/dL in all healthy dogs and >5 μg/dL in all dogs in which HA was excluded. None of the dogs with HA showed a cortisol‐increase above the detection‐limit of the assay. After 6 hours, cortisol concentrations had decreased in the healthy and HC group and were back to baseline after 24 hours. Conclusions and Clinical Importance: The depot formulation can be used in place of the short‐acting ACTH to evaluate the adrenocortical reserve. Blood for peak cortisol concentrations should be drawn 3 hours after stimulation in cases in which HC is suspected; in HA‐suspected cases, blood sampling can take place after 1 hour. As the stimulatory effect is gone after 24 hours, interference with other hormonal tests is unlikely after that time.